Comparative effect of tacrolimus 0.1% ointment and clobetasol 0.05% ointment in patients with oral lichen planus - Giovanni Corrocher (Blackwell Synergy, 2008)
Background: Oral lichen planus (OLP) is considered to be an autoimmune disease of unknown aetiology that affects the mucosae, especially the oral cavity. Objective: We compared tacrolimus 0.1% ointment and clobetasol 0.05% ointment for the treatment of OLP. Patients and Methods: A total of 32 patients (20 females and 12 males; all white, Italian origin, mean age of 43.6 18.4 years; 16 patients per treatment group) were treated with tacrolimus or clobetasol ointment for 4 weeks in a randomized, double-blind, clinical trial. Pain severity, burning sensation, and mucosal lesion extension were assessed using a four-point scale. Results: At the end of the treatment period, symptom scores were significantly lower in the tacrolimus group than in the clobetasol group. Conclusion: The results of this study suggest that tacrolimus 0.1% ointment is more effective than clobetasol propionate 0.05% ointment in the treatment of OLP. However, other studies are needed to confirm the effectiveness of this treatment before it can be recommended for use in clinical practice.